RECRUITMENT MANAGEMENT FOR MEMBERS OF ARABIC LEARNING IN ARABIC LANGUAGE STUDENT ASSOCIATION - Falaqi, Muhamad Rizal; Ahda, Ahmad Fahmi Arif; Hilmi, Danial (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
We steered this research to explore the recruitment and selection management of members based on interests applied by the selection team in the Arabic language student association. This research was a case study with a qualitative approach. The data were collected by interview, documentation, and observation. The results revealed that students who took part in the selection were classified based on their interests or skills through interviews and tests conducted by the selection team. However, the selection team experienced 2 obstacles: 1) time constraints during the selection process, 2) obstacles after the recruitment process. The first obstacle was when some students did not know what interests they have and the second one was when the members lost their motivation and commitment to learn. These obstacles affect other members and the learning process in the Arabic language student association. Therefore, the right recruitment process will attract more members that meet the qualifications and influence the student association. Then, in turn, it will make students more creative, explore themselves, become generation of achievers.